Study the Effect of Friendly Environmental Materials Addition on Viscosity Index and Pour Point of Engine Diesel Lubricating Oil - Hameed, Taghreed Mahdi; Khudhair, Muna Mahmood; Abdulridha, Lamyaa Adnan (Al-Nahrain Journal of Science, 2018)
In this work, the effect adding of some vegetable oils to mineral oil on physical properties such as viscosity and pour point of mineral lubricating oil was studied. Some vegetable oils, like corn oil and castor oil were used. Engine lubricating oil (si-cf4 diesel oil) that produced in AL-Doura refinery was selected and used in this study. Viscosity and pour point measurements were tested by viscometer and pour point tester respectively. Deferent mixtures of castor oil and corn oil were prepared with mixing ratios ranging from (0-100)% at 80°C added to the Iraqi motor lubricating oil with a percentage ratio in the range of (0-6 ) % and the best results was obtained at percentage ratio of 6% and study the viscosity index and pour point of the resulting lubricant oil. It was found that the addition of the of vegetable oil gave lubrication oil has a viscosity index ranging (106-115) and pour point ranging (-14--18)°C. It was found that the effect of addition of corn and castor oil mixture to mineral oil was varied according to the ratio of that oils.